2015
DOI: 10.1371/journal.pone.0119608
|View full text |Cite
|
Sign up to set email alerts
|

Glycans Flanking the Hypervariable Connecting Peptide between the A and B Strands of the V1/V2 Domain of HIV-1 gp120 Confer Resistance to Antibodies That Neutralize CRF01_AE Viruses

Abstract: Understanding the molecular determinants of sensitivity and resistance to neutralizing antibodies is critical for the development of vaccines designed to prevent HIV infection. In this study, we used a genetic approach to characterize naturally occurring polymorphisms in the HIV envelope protein that conferred neutralization sensitivity or resistance. Libraries of closely related envelope genes, derived from virus quasi-species, were constructed from individuals infected with CRF01_AE viruses. The libraries we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 67 publications
(112 reference statements)
2
14
0
Order By: Relevance
“…As removing N-glycans from the V2/V4 domains was shown to significantly improve the immunogenicities of HIV-1 Env proteins 15,16 and the neutralization sensitivities of HIV-1/SIV viruses, 17 it is understandable that several HIV-1 CRF01_AE isolates were found to show slightly higher neutralization sensitivity by polyclonal antibodies in plasma of HIV-1-infected subjects. 18 Moreover, according to previous studies, the short V1/V2 and fewer PNGSs in V1/V2/V4 [19][20][21][22] are the major characteristics of mucosally transmitted founder viruses, hence our data emphasize the possibility that the fewer PNGSs in the V2 and V4 loops may contribute to the advantage of CRF01_AE in sexual transmission. To support this hypothesis, we compared the sexually and intravenously transmitted CRF01_AE-CN Env sequences.…”
Section: Discussionsupporting
confidence: 75%
“…As removing N-glycans from the V2/V4 domains was shown to significantly improve the immunogenicities of HIV-1 Env proteins 15,16 and the neutralization sensitivities of HIV-1/SIV viruses, 17 it is understandable that several HIV-1 CRF01_AE isolates were found to show slightly higher neutralization sensitivity by polyclonal antibodies in plasma of HIV-1-infected subjects. 18 Moreover, according to previous studies, the short V1/V2 and fewer PNGSs in V1/V2/V4 [19][20][21][22] are the major characteristics of mucosally transmitted founder viruses, hence our data emphasize the possibility that the fewer PNGSs in the V2 and V4 loops may contribute to the advantage of CRF01_AE in sexual transmission. To support this hypothesis, we compared the sexually and intravenously transmitted CRF01_AE-CN Env sequences.…”
Section: Discussionsupporting
confidence: 75%
“…We observed that SM111 selected for mutations in Vpu's transmembrane domain, alone or in combination with a mutation at Env codon 136 that is predicted to abolish a common N-linked glycosylation site adjacent to the V1-V2 loop (47). We observed that SM111 reduced extracellular, but not intracellular, p24…”
Section: Discussionmentioning
confidence: 87%
“…5), compared to outgrowth of control HIV-1 NL4.3 at day 4 in the absence of SM111. Bulk (direct) Sanger sequencing of the culture supernatant indicated that strain C featured both a premature stop codon in place of tryptophan 22 (W22*) in Vpu's transmembrane domain and a highly dominant N136Y variant substitution in Env gp120 that is predicted to abolish a common N-linked glycosylation site (47). Neither wild-type Vpu nor wild-type Env sequences were detected.…”
Section: Sm111mentioning
confidence: 99%
“…The wild-type JR-FL pseudovirus is highly resistant to neutralization in the TZM-bl assay by virtually all V2i, V2p, and V2q MAbs tested, which is why it was selected for analysis (Table 1). Since glycosylation of Env shields and stabilizes Env from Abs of many specificities (5,7,24,25), we first tested the effect on the neutralization sensitivity of JR-FL and its variants from which selected gp120 glycans had been deleted ( Fig. 1 to 3).…”
Section: Variable Effects Of Jr-fl Glycan Mutations On Neutralizationmentioning
confidence: 99%